Forced Selection of a Human Immunodeficiency Virus Type 1 Variant That Uses a Non-Self tRNA Primer for Reverse Transcription: Involvement of Viral RNA Sequences and the Reverse Transcriptase Enzyme - Abbink, Truus E. M. (American Society for Microbiology, 2004)
Human immunodeficiency virus type 1 uses the tRNA(3)(Lys) molecule as a selective primer for reverse transcription. This primer specificity is imposed by sequence complementarity between the tRNA primer and two motifs in the viral RNA genome: the primer-binding site (PBS) and the primer activation signal (PAS). In addition, there may be specific interactions between the tRNA primer and viral proteins, such as the reverse transcriptase (RT) enzyme. We constructed viruses with mutations in the PAS and PBS that were designed to employ the nonself primer tRNA(Pro) or tRNA(1,2)(Lys). These mutants exhibited a severe replication defect, indicating that additional adaptation of the mutant virus is required to accommodate the new tRNA primer. Multiple independent virus evolution experiments were performed to select for fast-replicating variants. Reversion to the wild-type PBS-lys3 sequence was the most frequent escape route. However, we identified one culture in which the virus gained replication capacity without reversion of the PBS. This revertant virus eventually optimized the PAS motif for interaction with the nonself primer. Interestingly, earlier evolution samples revealed a single amino acid change of an otherwise well-conserved residue in the RNase H domain of the RT enzyme, implicating this domain in selective primer usage. We demonstrate that both the PAS and RT mutations improve the replication capacity of the tRNA(1,2)(Lys)-using virus.